2005
DOI: 10.1093/pcp/pci019
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Vesicle Derived Directly from Endoplasmic Reticulum is Involved in the Transport of Vacuolar Storage Proteins in Rice Endosperm

Abstract: We found novel vesicles derived from rough endoplasmic reticulum (ER) in rice endosperm. The novel vesicles had characteristic structures different from that of the ER-derived protein body type I and the Golgi-derived dense vesicles. Immunocytochemical analysis revealed that the novel vesicles are derived directly from the aggregates of vacuolar storage proteins in the rough ER. In addition, BiP, an ER-resident molecular chaperone, was localized in the novel vesicles, but also in protein storage vacuoles (PSVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 22 publications
0
55
1
Order By: Relevance
“…Golgi-associated dense vesicles containing glutelin and globulin are readily evident in developing rice endosperm cells supporting a role for the Golgi apparatus in routing these storage proteins to the PSV (Krishnan et al 1990(Krishnan et al , 1992). An alternative direct ER to PSV pathway bypassing the Golgi (Hara-Nishimura et al 1998) has also been proposed in rice (Takahashi et al 2005). However, other than this single study, PAC-like vesicles similar to that observed in pumpkin have not been seen in other microscopic studies on rice protein body biogenesis (Krishnan et al 1990, 1992, Ogawa et al 1989.…”
Section: Introductionmentioning
confidence: 72%
“…Golgi-associated dense vesicles containing glutelin and globulin are readily evident in developing rice endosperm cells supporting a role for the Golgi apparatus in routing these storage proteins to the PSV (Krishnan et al 1990(Krishnan et al , 1992). An alternative direct ER to PSV pathway bypassing the Golgi (Hara-Nishimura et al 1998) has also been proposed in rice (Takahashi et al 2005). However, other than this single study, PAC-like vesicles similar to that observed in pumpkin have not been seen in other microscopic studies on rice protein body biogenesis (Krishnan et al 1990, 1992, Ogawa et al 1989.…”
Section: Introductionmentioning
confidence: 72%
“…Electron microscopy was conducted as described by Takahashi et al (12). Samples of RR, CR, and feces were fixed in 4% paraformaldehyde in 0.1 m phosphate buffer (pH 7.2) for 1 h at room temperature.…”
Section: Inmentioning
confidence: 99%
“…PAC vesicles are between 200 and 400 nm in diameter and consist of an electron-lucent outer region with internal vesicles and an inner core of storage protein aggregates. Rice contains compartments similar to PAC vesicles with a central core of storage proteins (glutelins and a-globulins in this case) and an outer translucent layer with vesicles, but they differ from PAC vesicles in being larger (;1 mm in diameter) and having ribosomes decorating their surface (Takahashi et al, 2005). In addition, physical connections between these compartments and the ER have been suggested based on EM images (Takahashi et al, 2005).…”
Section: Autophagy In Cereal Endosperm Cellsmentioning
confidence: 99%